# Question and Answers Forum

Others Questions

Question Number 100904 by Dwaipayan Shikari last updated on 29/Jun/20

$$\mathrm{li}\underset{\mathrm{n}\rightarrow\infty} {\mathrm{m}}\left[\frac{\left({n}+\mathrm{1}\right)\left({n}+\mathrm{2}\right)......\mathrm{3}{n}}{{n}^{\mathrm{2}{n}} }\right]^{\frac{\mathrm{1}}{{n}}} \\$$

Commented by Ar Brandon last updated on 29/Jun/20

I like how you transformed the sum directly into integral without decomposing it into simpler sums.��

Commented by Dwaipayan Shikari last updated on 29/Jun/20

$$\:{suppose}\:\:\:{y}={li}\underset{{n}\rightarrow\infty} {{m}}\left[\frac{\left({n}+\mathrm{1}\right)\left({n}+\mathrm{2}\right)....\mathrm{3}{n}}{{n}.{n}......\mathrm{2}{n}\:{times}}\right]^{\frac{\mathrm{1}}{{n}}} \\$$$$\\$$$${log}\:{y}=\frac{\mathrm{1}}{{n}}\:{li}\underset{{n}\rightarrow\infty} {{m}}\left[{log}\left(\mathrm{1}+\frac{\mathrm{1}}{{n}}\right)+{log}\left(\mathrm{1}+\frac{\mathrm{2}}{{n}}\right)+....+{log}\left(\mathrm{1}+\frac{\mathrm{2}{n}}{{n}}\right)\right] \\$$$$\\$$$${logy}=\frac{\mathrm{1}}{{n}}\:{li}\underset{{n}\rightarrow\infty\:} {{m}}\underset{{r}=\mathrm{1}} {\overset{\mathrm{2}{n}} {\sum}}{log}\left(\mathrm{1}+\frac{{r}}{{n}}\right) \\$$$${logy}=\int_{\mathrm{0}} ^{\mathrm{2}} {log}\left(\mathrm{1}+{x}\right){dx} \\$$$${logy}=\:\:\left[{xlog}\left(\mathrm{1}+{x}\right)\right]_{\mathrm{0}} ^{\mathrm{2}} −\int_{\mathrm{0}} ^{\mathrm{2}} \frac{{x}}{{x}+\mathrm{1}} \\$$$${logy}=\:\mathrm{2}{log}\mathrm{3}−\left[{x}−{log}\left({x}+\mathrm{1}\right)\right]_{\mathrm{0}} ^{\mathrm{2}} \\$$$${logy}=\mathrm{2}{log}\mathrm{3}−\mathrm{2}+{log}\mathrm{3} \\$$$${logy}=\mathrm{3}{log}\mathrm{3}−\mathrm{2} \\$$$$\:\:\:\:\:\:{y}=\:\:{e}^{\mathrm{3}{log}\mathrm{3}−\mathrm{2}} =\frac{\mathrm{27}}{{e}^{\mathrm{2}} } \\$$$$\\$$$${check}\:{this} \\$$

Commented by mscbed last updated on 29/Jun/20

$$\\$$

Answered by Ar Brandon last updated on 29/Jun/20

$${l}=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\left[\frac{\left(\mathrm{n}+\mathrm{1}\right)\left(\mathrm{n}+\mathrm{2}\right)...\left(\mathrm{n}+\mathrm{2n}\right)}{\mathrm{n}^{\mathrm{2n}} }\right]^{\frac{\mathrm{1}}{\mathrm{n}}} =\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\left[\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{n}}\right)\left(\mathrm{1}+\frac{\mathrm{2}}{\mathrm{n}}\right)\centerdot\centerdot\centerdot\left(\mathrm{1}+\frac{\mathrm{2n}}{\mathrm{n}}\right)\right]^{\frac{\mathrm{1}}{\mathrm{n}}} \\$$$$\Rightarrow{l}=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\prod}}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)^{\frac{\mathrm{1}}{\mathrm{n}}} \Rightarrow\mathrm{ln}{l}=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}ln}\left\{\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\prod}}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)^{\frac{\mathrm{1}}{\mathrm{n}}} \right\} \\$$$$\Rightarrow\mathrm{ln}{l}=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\sum}}\left\{\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)^{\frac{\mathrm{1}}{\mathrm{n}}} \right\}=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{1}}{\mathrm{n}}\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\sum}}\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right) \\$$$$\:\:\:\:\:\:\:\:\:\:\:=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{1}}{\mathrm{n}}\left\{\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{n}} {\sum}}\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)+\underset{\mathrm{k}=\mathrm{n}+\mathrm{1}} {\overset{\mathrm{2n}} {\sum}}\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)\right\} \\$$$$\:\:\:\:\:\:\:\:\:\:\:=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{1}}{\mathrm{n}}\left\{\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{n}} {\sum}}\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)+\underset{\mathrm{p}=\mathrm{1}} {\overset{\mathrm{n}} {\sum}}\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{n}+\mathrm{p}}{\mathrm{n}}\right)\right\} \\$$$$\:\:\:\:\:\:\:\:\:\:\:=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{1}}{\mathrm{n}}\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{n}} {\sum}}\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)+\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{1}}{\mathrm{n}}\underset{\mathrm{p}=\mathrm{1}} {\overset{\mathrm{n}} {\sum}}\mathrm{ln}\left(\mathrm{2}+\frac{\mathrm{p}}{\mathrm{n}}\right) \\$$$$\:\:\:\:\:\:\:\:\:\:\:=\int_{\mathrm{1}} ^{\mathrm{2}} \mathrm{lnxdx}+\int_{\mathrm{2}} ^{\mathrm{3}} \mathrm{lnxdx}=\left[\mathrm{x}\left(\mathrm{lnx}−\mathrm{1}\right)\right]_{\mathrm{1}} ^{\mathrm{2}} +\left[\mathrm{x}\left(\mathrm{lnx}−\mathrm{1}\right)\right]_{\mathrm{2}} ^{\mathrm{3}} \\$$$$\:\:\:\:\:\:\:\:\:\:\:=\mathrm{2}\left(\mathrm{ln2}−\mathrm{1}\right)+\mathrm{1}+\mathrm{3}\left(\mathrm{ln3}−\mathrm{1}\right)−\mathrm{2}\left(\mathrm{ln2}−\mathrm{1}\right)=\mathrm{3ln3}−\mathrm{2} \\$$$$\Rightarrow{l}=\mathrm{e}^{\mathrm{3ln3}−\mathrm{2}} =\frac{\mathrm{3}^{\mathrm{3}} }{\mathrm{e}^{\mathrm{2}} }\Rightarrow\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\left[\frac{\left(\mathrm{n}+\mathrm{1}\right)\left(\mathrm{n}+\mathrm{2}\right)...\left(\mathrm{n}+\mathrm{2n}\right)}{\mathrm{n}^{\mathrm{2n}} }\right]^{\frac{\mathrm{1}}{\mathrm{n}}} =\frac{\mathrm{27}}{\mathrm{e}^{\mathrm{2}} } \\$$

Answered by mathmax by abdo last updated on 29/Jun/20

$$\mathrm{let}\:\mathrm{A}_{\mathrm{n}} =\left\{\frac{\left(\mathrm{n}+\mathrm{1}\right)\left(\mathrm{n}+\mathrm{2}\right)....\left(\mathrm{n}+\mathrm{2n}\right)}{\mathrm{n}^{\mathrm{2n}} }\right\}^{\frac{\mathrm{1}}{\mathrm{n}}} \:\Rightarrow\mathrm{lnA}_{\mathrm{n}} =\frac{\mathrm{1}}{\mathrm{n}}\mathrm{ln}\left(\frac{\prod_{\mathrm{k}=\mathrm{1}} ^{\mathrm{2n}} \left(\mathrm{n}+\mathrm{k}\right)}{\mathrm{n}^{\mathrm{2n}} }\right) \\$$$$=\frac{\mathrm{1}}{\mathrm{n}}\left\{\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{2n}} \mathrm{ln}\left(\mathrm{n}+\mathrm{k}\right)−\mathrm{2nln}\left(\mathrm{n}\right)\right\}=\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{2n}} \mathrm{ln}\:\left(\mathrm{n}+\mathrm{k}\right)−\mathrm{2ln}\left(\mathrm{n}\right) \\$$$$=\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{2n}} \left(\:\mathrm{lnn}+\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)\right)−\mathrm{2ln}\left(\mathrm{n}\right)\:=\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{2n}} \mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right) \\$$$$=\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}−\mathrm{1}} \mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)\:+\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{n}} ^{\mathrm{2n}} \:\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)\left(\rightarrow\mathrm{p}=\mathrm{k}−\mathrm{n}\right) \\$$$$=\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}−\mathrm{1}} \mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)\:+\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{p}=\mathrm{0}} ^{\mathrm{n}} \:\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{p}+\mathrm{n}}{\mathrm{n}}\right) \\$$$$=\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}−\mathrm{1}} \mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)+\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{p}=\mathrm{0}} ^{\mathrm{n}} \:\mathrm{ln}\left(\mathrm{2}+\frac{\mathrm{p}}{\mathrm{n}}\right)\:\:\mathrm{we}\:\mathrm{have} \\$$$$\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{k}=\mathrm{1}} ^{\mathrm{n}−\mathrm{1}} \mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)\rightarrow\int_{\mathrm{0}} ^{\mathrm{1}} \:\mathrm{ln}\left(\mathrm{1}+\mathrm{x}\right)\mathrm{dx}\:=_{\mathrm{1}+\mathrm{x}=\mathrm{t}} \:\:\int_{\mathrm{1}} ^{\mathrm{2}} \:\mathrm{ln}\left(\mathrm{t}\right)\mathrm{dt}\:=\left[\mathrm{tlnt}−\mathrm{t}\right]_{\mathrm{1}} ^{\mathrm{2}} \\$$$$=\mathrm{2ln}\left(\mathrm{2}\right)−\mathrm{2}+\mathrm{1}\:=\mathrm{2ln}\left(\mathrm{2}\right)−\mathrm{1} \\$$$$\frac{\mathrm{1}}{\mathrm{n}}\sum_{\mathrm{p}=\mathrm{0}} ^{\mathrm{n}} \:\mathrm{ln}\left(\mathrm{2}+\frac{\mathrm{p}}{\mathrm{n}}\right)\rightarrow\int_{\mathrm{0}} ^{\mathrm{1}} \:\mathrm{ln}\left(\mathrm{2}+\mathrm{x}\right)\mathrm{dx}\:=_{\mathrm{2}+\mathrm{x}=\mathrm{t}} \:\:\int_{\mathrm{2}} ^{\mathrm{3}} \mathrm{ln}\left(\mathrm{t}\right)\mathrm{dt}=\left[\mathrm{tlnt}−\mathrm{t}\right]_{\mathrm{2}} ^{\mathrm{3}} \\$$$$=\mathrm{3ln}\left(\mathrm{3}\right)−\mathrm{3}−\mathrm{2ln}\left(\mathrm{2}\right)+\mathrm{2}\:=\mathrm{3ln}\left(\mathrm{3}\right)−\mathrm{2ln}\left(\mathrm{2}\right)−\mathrm{1}\:\Rightarrow \\$$$$\mathrm{lim}_{\mathrm{n}\rightarrow+\infty} \mathrm{lnA}_{\mathrm{n}} =\mathrm{2ln}\left(\mathrm{2}\right)−\mathrm{1}+\mathrm{3ln}\left(\mathrm{3}\right)−\mathrm{2ln}\left(\mathrm{2}\right)−\mathrm{1}\:=\mathrm{3ln}\left(\mathrm{3}\right)−\mathrm{2}\:\Rightarrow \\$$$$\mathrm{lim}_{\mathrm{n}\rightarrow+\infty} \:\mathrm{A}_{\mathrm{n}} =\mathrm{e}^{\mathrm{3ln}\left(\mathrm{3}\right)−\mathrm{2}} \:=\mathrm{9e}^{−\mathrm{2}} \:=\frac{\mathrm{9}}{\mathrm{e}^{\mathrm{2}} } \\$$$$\\$$

Commented by mathmax by abdo last updated on 29/Jun/20

$$\mathrm{sorry}\:\mathrm{lim}_{\mathrm{n}\rightarrow+\infty} \:\:\mathrm{A}_{\mathrm{n}} =\mathrm{27}\:\mathrm{e}^{−\mathrm{2}} \:=\frac{\mathrm{27}}{\mathrm{e}^{\mathrm{2}} } \\$$

Answered by Ar Brandon last updated on 29/Jun/20

$$\\$$$$\mathrm{A}_{\mathrm{n}} =\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\left[\frac{\left(\mathrm{n}+\mathrm{1}\right)\left(\mathrm{n}+\mathrm{2}\right)...\left(\mathrm{n}+\mathrm{2n}\right)}{\mathrm{n}^{\mathrm{2n}} }\right]^{\frac{\mathrm{1}}{\mathrm{n}}} =\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\left[\left(\mathrm{1}+\frac{\mathrm{1}}{\mathrm{n}}\right)\left(\mathrm{1}+\frac{\mathrm{2}}{\mathrm{n}}\right)\centerdot\centerdot\centerdot\left(\mathrm{1}+\frac{\mathrm{2n}}{\mathrm{n}}\right)\right]^{\frac{\mathrm{1}}{\mathrm{n}}} \\$$$$\Rightarrow\mathrm{A}_{\mathrm{n}} =\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\prod}}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)^{\frac{\mathrm{1}}{\mathrm{n}}} \Rightarrow\mathrm{lnA}_{\mathrm{n}} =\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}ln}\left\{\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\prod}}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)^{\frac{\mathrm{1}}{\mathrm{n}}} \right\} \\$$$$\Rightarrow\mathrm{lnA}_{\mathrm{n}} =\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\sum}}\left\{\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right)^{\frac{\mathrm{1}}{\mathrm{n}}} \right\}=\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\frac{\mathrm{1}}{\mathrm{n}}\underset{\mathrm{k}=\mathrm{1}} {\overset{\mathrm{2n}} {\sum}}\mathrm{ln}\left(\mathrm{1}+\frac{\mathrm{k}}{\mathrm{n}}\right) \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\int_{\mathrm{1}} ^{\mathrm{3}} \mathrm{lnxdx}=\left[\mathrm{x}\left(\mathrm{lnx}−\mathrm{1}\right)\right]_{\mathrm{1}} ^{\mathrm{3}} =\mathrm{3}\left(\mathrm{ln3}−\mathrm{1}\right)−\left(\mathrm{ln1}−\mathrm{1}\right) \\$$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:=\mathrm{3ln3}−\mathrm{3}+\mathrm{1}=\mathrm{3ln3}−\mathrm{2}\Rightarrow{l}=\mathrm{e}^{\mathrm{3ln3}−\mathrm{2}} =\frac{\mathrm{3}^{\mathrm{3}} }{\mathrm{e}^{\mathrm{2}} } \\$$$$\Rightarrow\underset{\mathrm{n}\rightarrow\infty} {\mathrm{lim}}\left[\frac{\left(\mathrm{n}+\mathrm{1}\right)\left(\mathrm{n}+\mathrm{2}\right)...\left(\mathrm{n}+\mathrm{2n}\right)}{\mathrm{n}^{\mathrm{2n}} }\right]^{\frac{\mathrm{1}}{\mathrm{n}}} =\frac{\mathrm{27}}{\mathrm{e}^{\mathrm{2}} } \\$$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com